The Mechanism of Long Non-coding RNA in Cancer Radioresistance/Radiosensitivity: A Systematic Review - Wu, Wenhan; Zhang, Shijian; He, Jia (Frontiers in Pharmacology, 2022)
Background and purpose: Radioresistance remains a significant challenge in tumor therapy. This systematic review aims to demonstrate the role of long non-coding RNA (lncRNA) in cancer radioresistance/radiosensitivity. Material and methods: The electronic databases Pubmed, Embase, and Google Scholar were searched from January 2000 to December 2021 to identify studies addressing the mechanisms of lncRNAs in tumor radioresistance/sensitivity, each of which required both in vivo and in vitro experiments. Results: Among the 87 studies identified, lncRNAs were implicated in tumor radioresistance/sensitivity mainly in three paradigms. (1) lncRNAs act on microRNA (miRNA) by means of a sponge, and their downstream signals include some specific molecular biological processes (DNA repair and chromosome stabilization, mRNA or protein stabilization, cell cycle and proliferation, apoptosis-related pathways, autophagy-related pathways, epithelial-mesenchymal transition (EMT), cellular energy metabolism) and some signaling mediators (transcription factors, kinases, some important signal transduction pathways) that regulate various biological processes. (2) lncRNAs directly interact with proteins, affecting the cell cycle and autophagy to contribute to tumor radioresistance. (3) lncRNAs act like transcription factors to initiate downstream signaling pathways and participate in tumor radioresistance. Conclusion: lncRNAs are important regulators involved in tumor radioresistance\sensitivity. Different lncRNAs may participate in the radioresistance with the same regulatory paradigm, and the same lncRNAs may also participate in the radioresistance in different ways. Future research should focus more on comprehensively characterizing the mechanisms of lncRNAs in tumor radioresistance to help us identify corresponding novel biomarkers and develop new lncRNA-based methods to improve radioresistance.